Rediscovery of the enigmatic Andean frog Telmatobius halli Noble (Anura: Telmatobiidae), re-description of the tadpole and comments on new adult’s characters, type locality and conservation status - Cuevas, C.c.; Formas, J.r.; Alvarado-Rybak, M.; Peñafiel-Ricaurte, A.; Azat, C. (Zootaxa, 2020)
We report the rediscovery of Telmatobius halli (Hall’s water frog), which had not been found since its description (over 80 years) since its type locality was not clearly established. “Aguas Calientes” near Ollagüe is hypothesized as the original type locality where Frank Gregory Hall collected the type material in 1935. The tadpole is re-described, and new data on the external and internal morphology of adults is provided. These new morphological data are compared with Telmatobius spp. inhabiting geographically close to T. halli in Chile and Bolivia. In addition, comments on its ecology, conservation, and taxonomic status in relation with other Telmatobius spp. inhabiting nearby areas in Ascotán and Carcote salt pans are provided. No evidence of Batrachochytrium dendrobatidis and Ranavirus infection was found in T. halli and a sympatric amphibian species. Our work supports the validity of T. halli and suggests this species should be considered as Data Deficient in the IUCN Red List assessment until taxonomic issues are resolved.